Optimasi Kinerja Sensor Ultrasonik pada Prototype Sistem Monitoring Slot Parkir - Fitriani, Fitriani; Saenong, Andi; Idris, Mochammad Agus; Justam, Justam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The growth of private vehicles in urban areas poses significant challenges in managing parking spaces efficiently and accurately. The Internet of Things (IoT) technology offers a promising solution for developing an automated parking slot monitoring system based on sensors. This study aims to optimize the performance of ultrasonic sensors by evaluating two different installation positions: at the rear (Scenario A) and above (Scenario B) the parking slot. The research was conducted using an experimental approach with a miniature prototype, where data were collected and evaluated based on detection accuracy. The results showed that Scenario B achieved an accuracy of 85%, whereas Scenario A reached only 55%, with a 30% accuracy difference. These findings indicate that sensor placement greatly influences system performance in detecting the presence of vehicles. This study provides a significant contribution to the development of more accurate and efficient IoT-based automated parking systems.